2018
DOI: 10.3390/app8122500
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium Sulfate Type on Evolution of Reaction Products and Strength in NaOH- and CaO-Activated Ground Granulated Blast-Furnace Slag

Abstract: This study investigated the influences of CaSO4 type (i.e., anhydrite vs. gypsum) on strength development and reaction products in the activation of ground granulated blast-furnace slag (GGBFS) when different activators (i.e., CaO vs. NaOH) and sources of GGBFS were used. In the CaO-activation, the addition of calcium sulfates greatly enhanced 28-day strengths, regardless of the choice of CaSO4 or GGBFS source, through increasing the quantities of reaction products and reducing pore volume and size. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…(3) Research on the control mechanism of efflorescence of waste gypsum-alkali slag cement cementitious material system. There are differences in the sensitivity of waste gypsum and GBFS to different types of activators [42]. The performance of cement will also change with the change of the activator.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Research on the control mechanism of efflorescence of waste gypsum-alkali slag cement cementitious material system. There are differences in the sensitivity of waste gypsum and GBFS to different types of activators [42]. The performance of cement will also change with the change of the activator.…”
Section: Discussionmentioning
confidence: 99%
“…GY ionizes and releases Ca 2+ and SO4 2to a reaction system and is hence expected to improve the performance of the FA-GGBS-based alkali-activated system. However, few studies have shown detrimental effects on compressive strength depending on the proportion of the GY in the binders and the characteristics of the activators used [21][22][23][24]. Gypsum has been used as a sulfate activator in FA/slag-based geopolymer pastes, which created favorable conditions for the diffusion and penetration of ions for the activation of FA/slag precursors and led to the formation of ettringite [25].…”
Section: Introductionmentioning
confidence: 99%